‘Cracks’ in the scholarly communications system: Insights from a longitudinal international study of early career researchers - Nicholas, David; Boukacem-Zeghmouri, Cherifa; Rodriguez-Bravo, Blanca; Herman, Eti; Abrizah, Abdullah; Clark, David; Serbina, Galina; Sims, David; Świgon, Marzena; Xu, Jie; Watkinson, Anthony; Jamali, Hamid R.; et al. (Learned publishing)
170 early career researchers interviewed three times over 2 years, have uniquely contributed towards a stress test of scholarly communications and cracks have been identified. The perfect storm created by the convergence of millennial values and the pandemic appears to have fast-forwarded the cracking process, perhaps, for the good. The cracks in question are: (1) peer review; (2) reputational assessment; (3) unethical/questionable practices; (4) collaboration; (5) networking.